Teachers' Perceptions Of Acts Of Violence In The Primary School Education Environment - Laurentius Ni; Hendrikus Maku; Ambros Leonangung Edu; Nesibe AĞIRMAN (Jurnal Ilmu Pendidikan, 2025)
This research aims to describe teachers' perceptions of acts of violence in elementary schools, with a focus on the North Lamba Leda sub-district, East Manggarai Regency. Quantitative methods were used in this research, by conducting a survey via questionnaire to the elementary school teachers involved. The data obtained from the questionnaire will be analyzed to identify the views and experiences of teachers regarding violence in education. The results of the research show that the majority of teachers in elementary schools in this sub-district have witnessed violence among students in their schools. This phenomenon is considered a serious problem that must be addressed to ensure a safe and nurturing educational environment for children. Violence in education not only harms students physically and psychologically, but also reflects the social pathology that occurs in the school environment, as well as highlighting deficiencies in the essence of education which should promote humanist values and respect individual dignity. By understanding teachers' perceptions of violence in education, this research provides valuable insights for the development of educational policies and practices that are more responsive and oriented towards child protection and creating safe and supportive learning environments for student growth and development. Efforts to overcome violence in education must be a priority in improving the education system and creating a more just and cultured society.